1990
DOI: 10.1093/nar/18.15.4626
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of core and envelope genes of the hepatitis C virus genome derived directly from human healthy carriers

Abstract: Hepatitis C virus (HCV) is the major causative agent of post transfusion non-A, non-B hepatitis throughout the world. We isolated and sequenced cDNA clones of the HCV genome from RNA extracted from healthy Japanese HCV carrier plasma samples by reverse polymerase chain reaction (rPCR) methods (1, 2). Primers were designed from the nucleotide sequence of HCV derived from an experimentally transmitted chimpanzee (3, 4). Here we report the complete nucleotide and amino acid sequences of the structural gene of HCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(44 citation statements)
references
References 2 publications
0
44
0
Order By: Relevance
“…Partial sequence data from the putative structural region of various HCV isolates has been reported recently (25,28). Fig.…”
Section: Gctt Tgtacgacgtggttacaaagctcccc Ttggccgtgatgggmagctcctacggatmentioning
confidence: 99%
See 1 more Smart Citation
“…Partial sequence data from the putative structural region of various HCV isolates has been reported recently (25,28). Fig.…”
Section: Gctt Tgtacgacgtggttacaaagctcccc Ttggccgtgatgggmagctcctacggatmentioning
confidence: 99%
“…1) is compared with that from three Japanese isolates. HC-J1 was derived from a blood donor (28), HC-J4 was from an isolate passaged in chimpanzees (28), and JH-1 was from a healthy human carrier (25). Amino acids identical with HCV-1 are indicated by horizontal lines and the numbering is according to that in Fig.…”
Section: Mstnpkpqkknkrntnrrpqdvkfpgggqivggvyllprrgprigvratrktsersqprgmentioning
confidence: 99%
“…HCV has a positivestranded RNA as its genome. Nucleotide sequence analyses of HCV clones isolated in different places in the world revealed that there are significant sequence diversities (8)(9)(10)(11)(12)(13)(14)(15). The analysis of the region of non-structure 5 (NS5) of the HCV genome found, at least five different HCV genotypes in the world (16).…”
Section: Introductionmentioning
confidence: 99%
“…The genome encodes two putative structural proteins which are translated from sequences in the vicinity of the 5' terminus of the genome: nucleocapsid protein, containing a number of basic amino acids, and envelope protein, containing nine potential glycosylation sites. Nonstructural proteins NS1 to NS5 are translated from the coding region immediately following the envelope gene (Okamoto et al, 1990 a;Kato et al, 1990;Takeuchi et al, 1990a;Takamizawa et al, 1991).…”
Section: Introductionmentioning
confidence: 99%